World heritage and the scientific consecration of 'outstanding universal value'. (April 2017) - Schmutz, Vaughn; Elliott, Michael A.
Since World War II, the world heritage movement generated widespread support for preserving various sites of natural and cultural significance deemed to have outstanding universal value (OUV) for humanity. While the designation and evaluation of OUV were initially ambiguous, this process underwent expansive rationalization over time. Building on world society scholarship, we argue that specialized international nongovernmental organizations (INGOs) played a particularly prominent role in defining OUV, formalizing the process of evaluation, and reinforcing the legitimacy of world heritage by promoting scientific standards and techniques. To support these claims, we systematically examine 811 'advisory body' evaluations produced by associated INGOs from 1980 to 2010 to illustrate (a) the expansive rationalization of evaluative procedures related to world heritage and (b) the increasing reliance on scientific legitimacy to define and validate OUV, particularly for cultural sites. Overall, our findings lend support to institutional theories of globalization.